Egg Consumption, Multi-Domain Cognitive Performance, and Short-Term Cognitive Change in a Representative Sample of Older U.S. Adults. (18th August 2019) - Bishop, Nicholas J.; Zuniga, Krystle E.
Abstract: Objective: Existing research supports a positive relationship between egg intake and cognitive function in older populations, although the impact of whole egg consumption on multi-domain cognitive function and cognitive decline in representative samples of older adults has not been described. We examined the association between egg consumption, cognitive performance, and cognitive change in a representative sample of U.S. adults aged 65 and older. Methods: We drew observations from the 2012 and 2014 Health and Retirement Study and the recently released 2013 Health Care and Nutrition Study. The analytic sample contained 3835 respondents, representing a weighted population of 37, 806, 082 community-dwelling adults aged 65 and older in 2013. Multivariate path analytic models were used to estimate the association between egg consumption groups (none, ≤ 1 serving per week, 2–6 servings per week, ≥ 7 servings per week) and cognitive performance across domains of working memory, executive function, and global mental status. First-order autoregressive models were used to estimate cognitive change over the 2-year observational period. Follow-up analyses examined associations between egg consumption group, dietary patterns, and nutrient intake. Results: On average, older adults consumed 0.34 eggs per day ( SD  = 0.36). Although bivariate analyses suggested that moderate egg consumers had the best cognitive performance at baseline assessment, egg consumption was not associated with cognitive performance or cognitive change when adjusting models for covariates known to have a robust association with cognitive health. Conclusions: Our results suggest that egg consumption does not benefit, nor is detrimental to, the cognitive health of older adults. Further studies of whole egg consumption and cognitive performance would benefit from controlled experimental settings, longer follow-up periods to measure cognitive change, and assessment of both community-dwelling and institutionalized older adults.